Charpit’s method,xpq + yq
2 = 1
let S(x, y, z, p, q) = xpq + yq2 - 1.
Then Sx = pq, Sy = q2, Sz = 0.
"\\frac{dp}{S_x+pS_z} = \\frac{dq}{S_y+qS_z}"
"\\frac{dp}{pq} - \\frac{dq}{q^2} = 0"
"\\frac{qdp - pdq}{pq^2} = \\frac{1}{p}d(\\frac{p}{q}) = 0"
p/q = const = a
p = aq.
Putting this into the equation S=0, we have:
q2(ax+y) = 1
"q= \\frac{\\pm 1}{\\sqrt{ax+y}}"
"p = aq = \\frac{\\pm a}{\\sqrt{ax+y}}"
Putting these two formulas in the equation dz = pdx + qdy, we have:
"dz = \\pm\\frac{adx + dy}{\\sqrt{ax+y}} = \\pm d(2\\sqrt{ax+y})"
Integrating this equation, we finally get:
"z = \\pm 2\\sqrt{ax+y} + b"
Answer. "z = \\pm 2\\sqrt{ax+y} + b"
Comments
Leave a comment